Socio-Legal Impact of Covid-19 on Industrial Dispute Act, 1947; With Special Reference to Strike, Lock-Out, Lay-Off and Retrenchment - Dr. Sonali B. Abhang (International Journal of Advanced Science and Technology, 2020)
The Ministry of Home Affairs (MHA) had on 29th March issued an order under Section 10(2)(I) of the Disaster Management Act (DMA),2005, to mitigate the economic hardship of the migrant workers also directing all employers to pay wages to workers on due date without any deduction even if the establishment was closed during the lockdown period. But two firms, Nagreeka Exports Ltd and Ficus Pax Private Limited, and a Ludhiana-based association of MSMEs have petitioned the Supreme Court seeking quashing of the Centre’s order. The order, as the petitions claim, seems to violate Articles 14 and 19 of the Constitution, which relate to the right to equality before the law and the right to do business. Though, the government has not given any explanation for its move, but on 15th May 2020 the Supreme Court barring the government from taking any coercive action against companies not following the Home Ministry’s order on wage payment, it decided to withdraw it. Therefore, On 18th May 2020 all Orders issued by NEC (National Executive Committee headed by Home Secretary Ajay Bhalla) under Section 10(2)(I) of the Disaster Management Act, 2005, shall cease to have effect from 18.05.2020. But Commenting on the latest development, Virjesh Upadhyay, Genral Secretary of Bhartiya Mazdoor Sangh (BMS) and various Trade Unions said that this new order amounts to complete injustice to workers. “When the government is ensuring salary for others, there cannot be separate set of rules for workers. Ensuring livelihood and wages during the period of lockdown is the duty of the government,”